Implementation of ISO 9001:2000 quality management system as applied to gamma scanning technique for inspecting fractionning columns and related unit process operations - Sebastián Calvo, Carlos (2018)
Product manufacturers and service providers have to follow certain procedures and protocols to guarantee the quality products and services to satisfy consumer requirements. Standards contribute by making development, manufacturing and supply of products and services more efficient, safer and competitive. The quality assessment and quality control system in radioisotope applications consists of enhanced quality awareness, better presentation of documentation, establishment of standard operating manuals, and preparation of procedures for validation of methods, surveillance of method performance and formulation of protocols for experimental design and execution, regular qualification of personnel, client liaison and safety.